In order to access WAP SITE DEVELOPMENT ON-LINE LIBRARY CATALOG - Maria Maria Ulfa (JAKSTIK Journal, 2004)
Library is one library in terms of a fairly complete collection of books, magazines, VCD, andcassette which is supported also by accessing the service catalog via the Internet. However,not all library users can access them by because they do not have personal internet access, aswell as for those who are mobile. For that, they need the service WAP (Wireless ApplicationProtocol) to make information access library catalogs, more practical and easier, but still ableto provide important information needed in the form of a book title, author name, book status,no.panggil books and no. parent books as well as the location where and how the book wason the floor, in accordance with the existing data in a database. Results from Catalog AccessLibrary Services Development using WAP is, capable of carrying out the process of findingbooks and ordering books for every book that was borrowed, so that during this process isstill done manually, can be done faster and more practical.